PENGARUH MEDIA VIDEO ANIMASI TERHADAP MOTIVASI DAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS II DI SDN 116 PEKANBARU - Ayuni, Nola Sri; Dafit, Febrina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was written with the aim of finding out the influence of animated video media on the motivation and learning outcomes of Indonesian language class II students at SDN 116 Pekanbaru. This quasi-experimental research uses a pretest posttest control group design. The number of respondents was 72 people. The instrument for collecting data on learning motivation is a questionnaire, and the instrument for collecting data on learning outcomes is a test. The data were analyzed using parametric statistics, namely the Independent Sample T-Test. The result is that there is an influence of animated video media on the motivation to learn Indonesian for class II students at SDN 116 Pekanbaru due to Sig.(2-tailed) 0.001 < 0.05. There is an influence of animated video media on the Indonesian language learning outcomes of class II students at SDN 116 Pekanbaru with Sig. (2-tailed) 0.001 < 0.05, indicated by the learning outcomes of students taught with animated video media which are higher than student motivation and learning outcomes. taught using powerpoint media.